The dramatic event in models of Fayez Khaddour’s poetry - جابر يوسف; الأسد رداح (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The dramatic poem represents a distinctive phenomenon in the course of modern Arab poetry because it carries the spirit of the age, and as a revolution against the prevailing poetic traditions, to come as a reflection of a tragic and dramatic reality of course. The event is the first element of drama, and because the drama is an act and the event is an act, the research found a great desire to know how to employ the event according to Fayez Khaddour, this poet who carried the homeland inside it, so that his homeland was one soul, suffering from him, him and from him. Fayez Khaddour achieved a distinguished presence in the dramatic poem, conveying his patriotic experience and suffering reflected on his painful self, in an artistic way that is not without poetic and lyrical despite its objectivity, and his poem took a modernist approach that brought us closer to the full poem, and this is why this research came to stand on the subject of the dramatic event In samples of his poems, they were distributed to an introduction, and to introduce the terms drama and event, and then research on the event in samples of Fayez Khaddour’s poetry, until it reached a conclusion that included the most prominent results he reached and then it was proven with sources and references